2010
DOI: 10.1007/s11745-010-3400-9
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Analysis of Chiral Anteiso Fatty Acids in the Polar and Neutral Lipids of Food

Abstract: Anteiso fatty acids (aFA) are substituted with a methyl group on the antepenultimate carbon of the straight acyl chain. This feature leads to a stereogenic center. The 12-methyltetradecanoic acid (a15:0) and the 14-methylhexadecanoic acid (a17:0) are the most common aFA found in food, although they occur only in very small quantities. In this study we used gas chromatography in combination with a chiral stationary phase to determine the enantiomeric distribution of both a15:0 and a17:0 in the neutral and polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(54 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…[38], [39] Natural sebastenoic acid was reduced by hydrogenation over 10% palladium on carbon to give 2,3,4,5-tetrahydrosebastenoic acid ( 2 ). Comparison of the optical rotation for 2 ([α] D 24  = −7.21) with the reported literature value for ( R )-12-methyltetradecanoic acid ([α] D 22  = −5.84) defined the absolute configuration at C12 as R .…”
Section: Resultsmentioning
confidence: 99%
“…[38], [39] Natural sebastenoic acid was reduced by hydrogenation over 10% palladium on carbon to give 2,3,4,5-tetrahydrosebastenoic acid ( 2 ). Comparison of the optical rotation for 2 ([α] D 24  = −7.21) with the reported literature value for ( R )-12-methyltetradecanoic acid ([α] D 22  = −5.84) defined the absolute configuration at C12 as R .…”
Section: Resultsmentioning
confidence: 99%
“…Without the availability of reference standards it turned out difficult to assess the enantiomeric excess of the chiral fatty acids with the exception of the anteisofatty acids. Previously, it was found that the S-anteiso-fatty acids were dominant in food [16,17]. However, in most occasions the R-enantiomer was detected as well.…”
Section: Enantioseparation Of Anteiso-fatty Acids In Vernix Caseosamentioning
confidence: 92%
“…In this study, we used this off-line RP-HPLC and GC/EI-MS technique to determine the fatty acids of vernix caseosa after conversion into the corresponding methyl esters. In addition, samples of vernix caseosa are known to contain a number of chiral fatty acids including anteiso-fatty acids which can be resolved by application of modified cyclodextrins [16][17][18]. The HPLC method was also found suitable to gather fractions simple enough for the direct enantioselective analysis by GC/EI-MS [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two remaining stereoisomers are enantiomers. Derived from other chiral fatty acids-for instance anteiso-fatty acids are known to be strongly enriched in the S-enantiomer [15], 4-alkylbranched fatty acids were R-enantiopure [16], and ricinoleic acid being R-enantiopure [17]-it was very likely that the SHFA were also non-racemic and may be enantiopure. For this reason, we attempted a determination of the optical rotation of FAME enriched from the native rapeseed and mustard oil (mixture of 21 SHFA).…”
Section: Chirality Of Shfa and Optical Rotation Measurementsmentioning
confidence: 99%